Inovasi Kurikulum Merdeka di Sekolah: Tantangan, dan Implikasinya Terhadap Peningkatan Kualitas Pendidikan - Khotimah, Siti Nur; Nurfaiza, Anni; Sukiman, Sukiman (Universitas PGRI Semarang, 2025)
This article examines the innovations implemented in the Independent Curriculum to improve the quality of education in Indonesia. Against the background of the limitations of the previous curriculum in preparing students to face the challenges of the 21st century, this article formulates two main problems: (1) what innovations are contained in the Independent Curriculum and (2) how do they impact the quality of education. This study uses a descriptive qualitative method with a literature study to analyze various sources related to curriculum development and learning tools. The purpose of this study is to explain the innovations contained in the Independent Curriculum and examine the opportunities, challenges, and impacts on the learning process in schools. The results of the study show that the Independent Curriculum offers flexible and inclusive learning methods, such as project-based learning, blended learning, and flipped classrooms. In addition, this curriculum focuses on developing students' critical, creative, and collaborative skills. Although there are challenges in its implementation, such as teacher understanding and limited resources, the Independent Curriculum has the potential to increase student motivation and form a more positive school culture, so that it can produce graduates who are ready to face social and economic changes.